TP53-induced glycolysis and apoptosis regulator (TIGAR) ameliorates lysosomal damage in the 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine-mediated mouse model of Parkinson's disease. (15th March 2021) - Ge, Jianbin; Lin, Hongyan; Yang, Jie; Li, QiQi; Zhou, Jingsi; Qin, Zhenghong; Wu, Feng
Highlights: Neurotoxin triggers TIGAR upregulation in early stage of MPTP/MPP + models of PD. TIGAR alleviates dopaminergic cell damage in MPTP/MPP + models of PD. TIGAR ameliorates oxidative stress in MPTP/MPP + models of PD. TIGAR blunts rupture of lysosome in MPTP/MPP + models of PD. Abstract: The progressive loss of dopaminergic (DA) neurons in the substantia nigra pars compacta (SNpc) correlates with rupture of lysosome in Parkinson's disease (PD). It has been found that TP53-induced glycolysis and apoptosis regulator (TIGAR) has been attributed to the regulation of metabolic pathways and neuroprotective effect. In the present study, we showed in a mouse model that 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP) caused lysosomal damage and DA neurons loss in the SNpc. MPTP only induced SP1-mediated TIGAR upregulation in the early stage of neurotoxin-induced pathology, and this compensatory mechanism was not enough to maintain normal lysosomal function. MPTP significantly decreased the levels of NADPH and GSH, and the effects were ameliorated by the expression of exogenous TIGAR but execerbated by knockdown of TIAGR. TIGAR or NADPH alleviated oxidative stress, rescued lysosomal dysfunction and attenuated DA neurons degeneration. Overexpression of TIGAR or NADPH supplement inhibited MPP + -mediated reactive oxygen species (ROS), lysosomal membrane permeabilization (LMP) and autophagic flux impairment in PC12 cells. Together, these findings suggest that TIGAR reduces MPTP-mediated oxidative stress, lysosomal depletion and DA neuron damage.